ANALISIS INVESTASI PADA TABUNGAN EMAS DI PEGADAIAN SYARIAH KOTA SINGKAWANG - Tania, Iwit; Radimin (Cross-Border Journal of Business Management, 2024)
This research is a type of field by using adescriptive gualiitative approach, namely research by conducting observations, interviews, and documentation to obtain data and then the data is analysed using technigues. The results of this study show that the analysis of investment in gold savings at the singkawang city pawnshop is very helpful for the community in the economy because the selling value of gold persists and every year it must rise and the selling value of gold remains even though we are in an are that can said to be far from urban areas in pegadaian syariah singkawang city by promoting savings gold has been running shoothly through brochures, banners and social media can reach a wider community. The savings investment pawnshop does not stipulate the amount of gold invested by the customer, is only reguired to meet a minimum blance of 0.1 grams at the time of opening the next account opening, the nature of which is easy to disburse is an advantage for each customer, can also make transactions through digital pawnshop applications, making tranactions easier. The sharia pawnshop has provided easy requirements, only with the requirements of an ID card, in a fairly good service, then a safety guarantee in the form of insurance. Inhibiting and supporting factors in investing in gold savings, the public’s ability to buy is still low, while the supporting factors for customers to invest with gold prices tend to rise quickly and are easy to liquidate.